Relations and Resistance of Authorities in Deforestation of Indigenous Forests in Kinipan Village, Central Borneo - Kartika, Ema; Nafisah, Jazilatun; Dzikrillah, Nurfaizzatu; Azkia, Rizka Noor; Kusumaningtyas, Zahra; Pramono, Didi (Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The Kinipan Indigenous Forest is both a livelihood and a vital habitat for indigenous peoples, animals, and plants. However, the presence of corporates has caused issues that have upset the equilibrium of the Kinipan Customary Forest. This research seeks to analyze the pattern of interactions that led to the admission of corporations into customary forests and to identify the resistance of the indigenous Kinipan people. Qualitative approach was employed, including observation collection techniques and data documentation from a Watchdoc Documentary-uploaded documentary video titled "KINIPAN," which is supported by literature studies. The findings of this study indicate the existence of a power relationship between the government and the company regarding the regulation of mining permits and mining roads in the Kinipan Customary Forest, which is carried out without the community's participation, thereby causing social conflict between third parties. As a result of this conflict, indigenous peoples formed multiple communities to defend the forest, including the forester's community, the Dayak Tomun community, and the Borneo Red Army.